A Simple Yet Effective Whole-Body Locomotion Framework for Quadruped Robots - Raiola, Gennaro; Mingo Hoffman, Enrico; Focchi, Michele; Tsagarakis, Nikos; Semini, Claudio (Frontiers in Robotics and AI, 2020)
In the context of legged robotics, many criteria based on the control of the Center of Mass (CoM) have been developed to ensure a stable and safe robot locomotion. Defining a whole-body framework with the control of the CoM requires a planning strategy, often based on a specific type of gait and a reliable state-estimation. In a whole-body control approach, if the CoM task is not specified, the consequent redundancy can still be resolved by specifying a postural task that set references for all the joints. Therefore, the postural task can be exploited to keep a well behaved, stable kinematic configuration. In this paper, we propose a generic locomotion framework which is able to generate different kind of gaits, ranging from very dynamic gaits such as the trot, to more static gaits like the crawl, without the need to plan the CoM trajectory. The framework is composed of a priority-based whole-body controller that works in synergy with a walking pattern generator. Thanks to a novel use of the postural task it was possible to completely remove the CoM task and thus the dependency on the estimation of floating base state, that is often prone to drift. We show the effectiveness of the framework by presenting simulations on different types of simulated terrains, including rough terrain, using different quadruped platforms.